Invasive acantholytic anaplastic extramammary Paget disease: A previously unreported neoplasm in the vulva and review of the literature - Flora Mae G. Sta. Ines; Julia R. Salinaro; Mary Marchese; Cara A. Mathews; M. Ruhul Quddus (Gynecologic Oncology Reports)
This report describes the first documented invasive acantholytic anaplastic extramammary Paget disease (AAEMPD) of the vulva. An 87-year-old female presented with a recurrent vulvar lesion refractory to topical imiquimod and treated with multiple wide local excisions (WLE). Microscopic examination of the final WLE specimen revealed unique histologic features, primarily supra-basal intraepidermal acantholysis with epidermal papillomatosis and hyperkeratosis. The epidermis, composed of two distinct cell populations, exhibited full-thickness atypia. Paget cells with high mitotic activity were present in the basal and parabasal layers surrounding benign squamous cells in the mid-squamous mucosa. The histologic features were suspicious of the EMPD involving a warty lesion and/or invasive squamous cell carcinoma. In addition to the intraepidermal component, dermal invasion was also present with lymphovascular space invasion. Immunohistochemical studies (KRT7, HER2, and GATA3 reactivity in Paget cells, p63 negativity, and rare mucin in Paget cells) supported the diagnosis of acantholytic anaplastic EMPD. AAEMPD, a rare variant of EMPD, shares similar prognosis and behavior with the classic Paget disease. Recognition and accurate diagnosis of this subtype is crucial for optimal patient management, given distinct treatment strategies compared with other entities in the differential diagnosis.